Biodegradation of Chlorsulfuron and Metsulfuron-Methyl by Aspergillus niger - Elisabetta Zanardini; Marco Negri; Giovanna Boschin; Alessandra D'Agostina; Anna Valle; Anna Arnoldi; Claudia Sorlini (The Scientific World Journal)
In this work, investigations were performed under laboratory conditions of the degradation ability by a common soil fungus, Aspergillus niger, toward chlorsulfuron and metsulfuron-methyl. The results were very encouraging (79% for chlorsulfuron and 61% for metsulfuron-methyl of total degradation), especially compared to those registered in our previous studies with a Pseudomonas fluorescens strain B2 (about 21 to 32%). Furthermore, the chemical degradation of the two compounds was studied and two products (1[2-methoxy-benzene-1-sulfonyl]-7-acetyltriuret and 1[2-chlorobenzene-1-sulfonyl]-7-acetyltriuret) were isolated and characterised by hydrolysis in acidic conditions. Our aim in the future will be the identification of intermediate metabolites by HPLC and LC-MS analyses in order to identify the degradative pathway by the fungal strain and to compare this to those obtained by chemical degradation and by P. fluorescens strain.